2016
DOI: 10.1071/rd16102
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and developmental programming of welfare and production traits in farm animals

Abstract: Abstract. The concept that postnatal health and development can be influenced by events that occur in utero originated from epidemiological studies in humans supported by numerous mechanistic (including epigenetic) studies in a variety of model species. Referred to as the 'developmental origins of health and disease' or 'DOHaD' hypothesis, the primary focus of large-animal studies until quite recently had been biomedical. Attention has since turned towards traits of commercial importance in farm animals. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 399 publications
(437 reference statements)
2
45
0
16
Order By: Relevance
“…Subsequent effects upon productivity include altered postnatal growth (Micke et al 2010a) and reproductive development (Sullivan et al 2009a;Mossa et al 2013). However, it is acknowledged that the effects of maternal nutrition during the periconception period and early gestation on fetoplacental development in cattle are poorly understood (Mossa et al 2015;Sinclair et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent effects upon productivity include altered postnatal growth (Micke et al 2010a) and reproductive development (Sullivan et al 2009a;Mossa et al 2013). However, it is acknowledged that the effects of maternal nutrition during the periconception period and early gestation on fetoplacental development in cattle are poorly understood (Mossa et al 2015;Sinclair et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, expression of different genes was affected, with particular focus on oxidative metabolism, apoptosis, endoplasmic reticulum stress and lipid metabolism. Furthermore, vast epigenetic erasure and reprogramming events take place during early embryogenesis (Dean et al, 2001;Smith et al, 2012), making the embryo also susceptible for epigenetic alterations. More in-depth research indeed confirms this by showing changes in DNA methylation after elevated NEFA exposure during embryo culture.…”
Section: What Happens With the Developing Zygote During The First Daymentioning
confidence: 99%
“…Numerous factors affect this intricate long play of reproductive physiology and will determine the cow's reproductive efficiency. Apart from the genetic trait effects, the nurture effects on reproductive capacities start in utero, and show to be also important during the calf and heifer rearing period (GonzalesRecio et al, 2012;Lohakare et al 2012;Sinclair et al, 2016). Many studies focused already on the effect of the conditions during the dry and the transition period on reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that sub-optimal maternal nutrition, stress or ill health during pregnancy can affect how offspring develop before birth, with implications for their later biology (Sinclair et al 2016). In farm animals, maternal state may therefore be an important contributor to health, welfare and productivity of progeny, and paying closer attention to gestation management could contribute to improvements in these parameters on farms (Rutherford et al 2012).…”
Section: Introductionmentioning
confidence: 99%